(untitled) (Journal of Environmental Science and Natural Resources, 2016)
Noise is one of the most pervasive environmental problems. Excessive noise has become one of the major concerning of urban life. Chittagong, the port city of Bangladesh, is one of the nosiest cities of the country. With economic development, the situation is expected to worsen farther. Motor vehicles are the principal source of noise pollution in the city. This study illustrates the level of noise pollution in Chittagong city corporation and its impacts on city dwellers. The noise level is measured at 25 locations of Chittagong city road areas. Time-weighted average noise levels have been measured at the roadside. From the study it was observed that the highest noise level in the roadside in Chittagong city was about 93dB found at AK Khan Circle and Agrabad circle, which far exceeded the acceptable limit of 60 dB set by the Government of Bangladesh. The level of noise pollution is closely related with traffic volume, particularly with the number of heavy vehicles like trucks, buses as well as auto rickshaw have been observed during the study. Questionnaire survey was done during the study to determine the health impacts on the city dwellers. Most of the common problems, the dweller suffering from noise pollution are headache, bad temper, sleeplessness, aggravation, hearing problems etc. J. Environ. Sci. & Natural Resources, 8(2): 37-40 2015